Development of Silicone Hydrogel Antimicrobial Contact Lenses with Mel4 Peptide Coating. Issue 10 (October 2018) - Dutta, Debarun; Kamphuis, Bjorn; Ozcelik, Berkay; Thissen, Helmut; Pinarbasi, Rasim; Kumar, Naresh; Willcox, Mark D. P.
Abstract : SIGNIFICANCE: This study investigated the development of an antimicrobial coating on silicone hydrogel contact lenses that may have the capacity to reduce contact lens–related infection and inflammatory events. PURPOSE: The purpose of this study was to develop an effective antimicrobial coating for silicone hydrogel contact lenses by attachment of Mel4 peptide. METHODS: Lotrafilcon A, comfilcon A, somofilcon A, senofilcon A, and lotrafilcon B silicone hydrogel contact lenses were plasma coated with acrylic acid followed by Mel4 antimicrobial peptide immobilization by covalent coupling. Peptide immobilization was quantified by x-ray electron spectroscopy. Contact lens diameter, base curve, center thickness, and lens surface wettability were measured by captive-bubble contact-angle technique. Antimicrobial activity of the lenses was determined against Pseudomonas aeruginosa and Staphylococcus aureus by viable plate count and also after soaking with artificial tears solution for 1 day. In vivo safety and biocompatibility were determined in an animal model for 1 week. RESULTS: Mel4 peptide–coated silicone hydrogel contact lenses were associated with high antimicrobial inhibition (>2 log), except for lotrafilcon B and senofilcon A. Lotrafilcon B did not exhibit any activity, whereas senofilcon A showed 1.4- and 0.7-log inhibition against P. aeruginosa and S. aureus, respectively. X-ray electron spectroscopy revealed significant increases in the lens surface–bound amide nitrogen in all contact lenses except for lotrafilcon B. All contact lens parameters remained unchanged except for the base curve and center thickness for senofilcon A. Mel4 immobilization was associated with a decrease in contact angle. Mel4-coated contact lens wear was not associated with any signs or symptoms of ocular irritation in a rabbit model study. Reduced antimicrobial activity was observed with all the lenses after soaking with artificial tears solution or rabbit wear. CONCLUSIONS: Mel4 antimicrobial coating may be an effective option for development of antimicrobial silicone hydrogel contact lenses.